IMPROVING MONGOLIA’S INVESTMENT CLIMATE AND ENHANCING ITS EFFICIENCY /A Comparative Study Based on Japan’s Experience/ - Dorjkhand, Molomjamts; Nagatomi, Takashi; Iwamoto, Koichi (Journal of Business and Innovation (Бизнес & Инноваци), 2026)
Investment constitutes a fundamental driver of economic growth, productivity enhancement, and national competitiveness. It represents an essential component of development strategy not only for developing economies but also for advanced industrialized nations seeking to sustain long-term economic expansion. In particular, foreign direct investment (FDI) generates multifaceted benefits, including technology transfer, managerial innovation, employment creation, and the strengthening of export capacity. The investment climate is a comprehensive and multidimensional concept encompassing political stability, legal certainty, institutional capacity, policy coherence, and infrastructure development. This study examines selected political and legal factors affecting Mongolia’s investment climate and undertakes a comparative analysis with Japan’s experience. By identifying institutional strengths and policy practices that have contributed to Japan’s investment environment, the paper seeks to propose practical and contextually appropriate measures for improving Mongolia’s investment framework and enhancing the overall effectiveness of foreign direct investment.